SU(4)LU(1)N model for the electroweak interactions - Pisano, F. [UNESP]; Pleitez, V. [UNESP] (American Physical Society (APS), 1995)
Assuming the existence of right-handed neutrinos, we consider an electroweak model based on the gauge symmetry SU(4)LU(1)N. We study the neutral currents coupled to all neutral vector bosons present in the theory. There are no flavor-changing neutral currents at the tree level, coupled with the lightest neutral vector boson. © 1995 The American Physical Society.